2014
DOI: 10.1007/s00213-014-3572-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid, GABAergic and hypothalamic pituitary adrenal (HPA) axis regulation: what is the current state of knowledge in humans?

Abstract: Rationale A robust epidemiological literature suggests an association between chronic stress and the development of affective disorders. However, the precise biological underpinnings of this relationship remain elusive. Central to the human response and adaptation to stress, activation and inhibition of the hypothalamic pituitary adrenal (HPA) axis involves a multi-level, multi-system, neurobiological stress response which is as comprehensive in its complexity as it is precarious. Dysregulation in this complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 202 publications
(270 reference statements)
2
65
0
1
Order By: Relevance
“…To the extent that lower ALLO and pregnanolone concentrations, especially following stress, are associated with diminished capacity to negatively modulate the HPA axis and facilitate its recovery following stress exposure (Guo et al 1995; Patchev et al 1996), then the blunted ALLO + pregnanolone stress response that was observed in our study sample may be one mechanism that may increase vulnerability to stress and stress-related illness (Crowley and Girdler 2014), including PPD. This may be particularly true for those women with a history of depressive illness, which is highly associated with chronic stress (Kendler et al 2000; McGuffin and Rivera 2015), and in whom we previously observed a blunted ALLO response to mental stress relative to never depressed women (Klatzkin et al 2006b).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…To the extent that lower ALLO and pregnanolone concentrations, especially following stress, are associated with diminished capacity to negatively modulate the HPA axis and facilitate its recovery following stress exposure (Guo et al 1995; Patchev et al 1996), then the blunted ALLO + pregnanolone stress response that was observed in our study sample may be one mechanism that may increase vulnerability to stress and stress-related illness (Crowley and Girdler 2014), including PPD. This may be particularly true for those women with a history of depressive illness, which is highly associated with chronic stress (Kendler et al 2000; McGuffin and Rivera 2015), and in whom we previously observed a blunted ALLO response to mental stress relative to never depressed women (Klatzkin et al 2006b).…”
Section: Discussionmentioning
confidence: 81%
“…These GABAergic neurosteroids, with cortisol, may therefore represent potential candidate mechanisms of PPD risk, since they each are stress responsive, are mutually regulatory during stress (Crowley and Girdler 2014; Mody and Maguire 2011), and are implicated in the development of both PPD and insomnia (Basta et al 2007; Schiller et al 2014; Teran-Perez et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…injections of CRF and ACTH in rats increase brain and plasma levels of allopregnanolone (Torres et al, 2001). These findings indicate that neuroactive steroids may play a crucial compensatory role in mediating homeostasis in response to stress (Biggio et al, 2007; Crowley and Girdler, 2014; Sarkar et al, 2011). …”
Section: Introductionmentioning
confidence: 85%
“…Among the most studied progesterone-derived neurosteroids in humans is ALLO, an A-ring-reduced metabolite of progesterone. ALLO is stress responsive in animals and humans (reviewed in (46)) and serves as a potent, positive allosteric modulator of GABA A receptors via dose-dependent enhancement of GABA-induced Cl-ion channels (47). GABA is the chief inhibitory neurotransmitter in the mammalian central nervous system.…”
Section: Introductionmentioning
confidence: 99%